Assessment of Tumor-Associated Tissue Eosinophilia (TATE) and Tumor-Associated Macrophages (TAMs) in Canine Transitional Cell Carcinoma of the Urinary Bladder - Rita Files; Victor Okwu; Nuno Topa; Marisa Sousa; Filipe Silva; Paula Rodrigues; Leonor Delgado; Justina Prada; Isabel Pires (Animals, 2024)
Transitional cell carcinoma of the urinary bladder is a significant neoplasm in dogs, characterized by a poor prognosis and a high metastatic potential. These canine spontaneous tumors share many characteristics with human transitional cell carcinoma, making them an excellent comparative model. The role of inflammatory infiltration in tumor development and progression is frequently contradictory, especially concerning tumor-associated tissue eosinophils (TATE) and tumor-associated macrophages (TAMs). This study aims to analyze TATE and TAMs in canine transitional cell carcinoma of the urinary bladder. Congo Red staining was used to identify TATE, and immunohistochemistry was performed to detect TAMs in 34 cases of canine transitional cell carcinoma of the bladder carcinomas, categorized into low and high grades. Statistically significant differences were observed between the number of eosinophils and macrophages in the two groups of tumors. The number of TATE was higher in low-grade malignant tumors, but the number of TAMs was higher in high-grade tumors. Our findings suggest the importance of TATEs and TAMs in the aggressiveness of canine transitional cell carcinoma and propose their potential use as therapeutic targets.